Efficient, One-Pot, BF3·OEt2-Mediated Synthesis of Substituted N-Aryl Lactams - Chaturvedi, Devdutt; Chaturvedi, Amit K.; Mishra, Nisha; Mishra, Virendra (Synlett, 2012)
A quick, efficient, one-pot, BF3·OEt2-mediated synthesis of substituted N-aryl lactams in good to excellent yields by reaction of various substituted arenes with a variety of ω-azido alkanoic acid chlorides at room temperature is reported.
Keywords: substituted arenes; ω-azido-alkanoic acid chloride; Lewis acid; N-aryl lactams